Pandora's picnic basket the potential and hazards of genetically modified foods - McHughen, Alan (Oxford University Press, 2000)
"Did you know that there are fish genes in some tomatoes? That Brazil nut genes in soybeans can result in potentially lethal allergic reactions? That rapeseed plants bred to be resistant to herbicides could become uncontrollable superweeds? Genetically modified foods do pose real risks, and in recent years they have become the focus of a pitched battle between scientists, entrepreneurs, consumer advocates, and environmentalists. Yet despite the great heat generated by the debate, there is very little real information on the subject, either about the technologies in use or about the regulatory processes established to protect us from potentially dangerous products." "Pandora's Picnic Basket explains, in clear and direct language, the technologies underlying genetically modified food, comparing them with other "natural" methods of plant breeding and production. Researcher Alan McHughen evaluated the safeguards in place from regulators around the world and asks whether these are sufficient. In particular, he examines the question of labeling, held by some to be an obvious way to help protect consumers, and addresses the honesty and usefulness of some of these labels. Throughout the book, McHughen offers fair-minded, well-informed accounts of issues of real concern, particularly environmental issues, and he outlines ways in which consumers can avoid genetically modified food if they so choose. The author uses question-and-answer boxes to address key issues and real case histories to illustrate the development and regulation of genetically modified food." "Genetically modified foods are increasingly available to the public. Pandora's Picnic Basket will help consumers make informed choices about this controversial technology."--Book jacket.